The Effect of Implementation of Pregnant Women's Class on Knowledge and Attitude of Pregnant Women about Preparation for Delivery in Puskesmas Kabanjahe, Karo Regency in 2022 - Imarina Tarigan (Science Midwifery, 2022)
Maternal Mortality Rate (MMR) is all deaths within that scope in every 100,000 live births. In addition to assessing maternal health programs, this indicator is also able to assess the degree of public health, because of its sensitivity to improving health services, both in terms of accessibility and quality (Kemenkes RI, 2021). Maternal Mortality Rate (MMR) in Sumatra Province North Year 2020 is 62.50 per 100,000 live births.This figure shows a decrease in MMR when compared to the previous year2019 which is 66.76 per 100,000 live births (202 cases out of 302,555 target for live births) (North Sumatra Provincial Health Office, 2020). Efforts to accelerate the decline in MMR are carried out by ensuring that every mother is able to access quality health services, such as health services for pregnant women, delivery assistance by trained health workers in health care facilities, postnatal care for mothers and babies, special care and referrals in case of complications, and family planning services, including postnatal family planning. Mothers and children are family members who need to get priority in the implementation of health efforts, because they are a vulnerable group. This is related to the phase of pregnancy, childbirth and postpartum in the mother and the phase of child development. This is the reason for the importance of maternal and child health efforts to be one of the priorities of health development in Indonesia (Kemenkes RI, 2018). This type of research is an experimental research with a quasi-experimental method, the research design is One-Group Pretest-Postest. The research sample was third trimester pregnant women who had attended classes for pregnant women as many as (4) meetings or face-to-face with a time according to the agreement between the midwife and pregnant women as many as 32 people. The results of the statistical test using t-test showed that the mean value based on the implementation of the pre-test class of pregnant women was 12.08 and after the implementation of the class of pregnant women 14.15 (post-test) there was a significant difference (p = 0.000 < 0, 05). Data analysis showed an increase in the mean (mean) knowledge of pregnant women before and after the implementation of the class for pregnant women.